EFEKTIVITAS DUKUNGAN VENTILASI TERHADAP PERBAIKAN POLA NAPAS PASIEN EFUSI PLEURA DI RUANG IGDRSUD LABUANG BAJI MAKASSAR - Muhammad Ilham Ismail; Sudarman; Suci Hardiyanti Suharto Putri; Syahrir Syahrir (Jurnal Kesehatan, 2025)
Pleural effusion is a condition of fluid accumulation in the pleural cavity that causes decreased lung expansion and disruption of breathing patterns. This disorder is often found in the Emergency Facility (IGD) and can cause severe shortness of breath and respiratory failure if not treated immediately. The purpose of the study was to determine the effectiveness of ventilation support on improving breathing patterns in pleural effusion patients in the emergency room of Labuang Baji Hospital Makassar. This study is a case report in a 59-year-old male patient with a diagnosis of pleural effusion. Nursing care is carried out according to SDKI, SLKI, and SIKI standards with a focus on three nursing diagnoses: ineffective breathing patterns, acute pain, and risk of infection. The main interventions include airway management, provision of ventilation support through a 5-liter nasal cannula per minute, pain management, and infection prevention. Results: after 8 hours of nursing intervention, there was an improvement in vital signs in the form of a decrease in breathing frequency, an increase in oxygen saturation from 91% to close to normal, reduced use of the respiratory support muscles, and an increase in patient comfort. Ventilation support has been shown to help improve oxygenation and improve the breathing patterns of pleural effusion patients. Ventilation support is effective as an initial measure in improving the breathing pattern of pleural effusion patients in the emergency room before definitive therapy is carried out.